Effect of microbiology handout on Amylolytic bacteria and Cellulolytic bacteria from vegetable waste soil on students' cognitive abilities - M. Nidhamul Maulana; Utami Sri Hastuti; Dwi Listyorini (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The scientific literacy framework in PISA 2015 includes context, competence, attitudes and knowledge. Knowledge is closely related to students' cognitive abilities. Analysis of needs in the class of 2020 Biology at the State University of Malang shows that 93.8% of students' knowledge about amylolytic and cellulolytic bacteria in vegetable waste disposal soil is relatively low. One factor is that there are no teaching materials related to this material. The research aims to determine the effectiveness and practicality of handouts in improving students' cognitive abilities. This research method is quasi-experimental with a nonrandomized pretest-posttest control group design—implementation in the control and ex-perimental classes by giving a pretest and posttest. The increase in posttest scores compared to the learning outcome scores for both classes was analyzed using the T-test to compare learning outcomes based on the N-gain score. The results of the unpaired t-test analysis stated that the cognitive abilities of students in the experimental class using handout were higher than those in the control class using PowerPoint—comparison value p-value (0.046) < α (0.05). The conclusion is that the handouts are practical and effective in improving students' cognitive abilities. Students can find out the existence of bacteria that play a role in the degradation process of starch and cellulose so that students can protect the environment and not throw away rubbish, which causes an imbalance in the soil ecosystem.Abstrak Kerangka kerja literasi sains dalam PISA 2015 meliputi konteks, kompetensi, sikap, dan pengetahuan. Pengetahuan erat hubungannya dengan kemampuan kogintif mahasiswa. Analisis kebutuhan di biologi angkatan 2020 Universitas Negeri Malang menunjukkan pengetahuan 93,8% mahasiswa tentang bakteri amilolitik dan bakteri selulolitik pada tanah pembuangan sampah sayur tergolong rendah. Salah satu faktornya adalah tidak ada bahan ajar terkait materi tersebut. Tujuan dari penelitian untuk mengetahui keefektifan dan kepraktisan handout dalam meningkatkan kemampuan kognitif mahasiswa. Metode penelitian ini kuasi eksperimen dengan desain nonrandomized pretest-posttest control group. Implementasi pada kelas kontrol dan kelas eksperimenn dengan diberikan pretest dan posttest. Peningkatan nilai posttest dibandingkan untuk nilai hasil belajar kedua kelas dan dianalisis dengan uji T untuk membandingkan hasil belajar berdasarkan N-gain skor. Hasil analisis uji-t tak berpasangan menyatakan kemampuan kognitif mahasiswa kelas eksperimen menggunakan handout lebih tinggi dibandingkan kelas kontrol menggunakan Power Point. Nilai perbandingan p-value (0,046) < α (0,05). Kesimpulannya adalah handout praktis dan efektif meningkatkan kemampuan kognitif mahasiswa. Mahasiswa dapat mengetahui keberadaan bakteri yang berperan dalam proses degradasi amilum dan selulosa, sehingga mahasiswa dapat menjaga lingkungan, tidak membuang sampah yang menyebabkan ketidakseimbangan ekosistem tanah.